(untitled) (Bulletin KNOB, 1996)
During the decades around 1300 a remarkably large group of towns was founded. In the province of Zeeland Brouwershaven (1285) and Arnemuiden (1288) were granted charters and in Gelre, in the Veluwe region, and in the northern point of it, Staverden (1298) and Hattem (1299). In the river area south of Utrecht, at that time the border region between the domains of Holland, Het Sticht and Gelre, a whole series of small towns was founded, among which Nieuwpoort (1283), Wijk-bij-Duurstede (1300), Asperen (circa 1313) and Culemborg (1318). In all probability they were bastion towns. A bastion town or new town was a political and economic power base founded from ideological motives. A town was deliberately planned by a person, a monarch, a sovereign, a vassal, often on virgin territory. Prestige, the symbolic sealing of power relations and territorial demarcation played an important part. In this article it is argued that Floris V (1256-1296) gave a new impulse to the foundation of new towns shortly before 1300. In cooperation with two local noblemen and his closest advisor Nicolaas van Cats (1270-1283) he founded Nieuwpoort around 1280. A few years later Brouwershaven and Arnemuiden followed. All three towns were founded as power bases of the count in contested regions. Floris followed the example of his English ally, king Edward I (1272-1307), who founded many new towns in contested border regions both in southwest France and in England and Wales. Just as the Dutch count conceived his residence, the ’Grote Zaal’ (Large Hall) in The Hague and some fortresses after the example of English royal architecture, he also adopted the town planning of the English monarch. Thus he presented himself as the equal of a ’foreign’, really powerful monarch. Circa 1300 Reinoud I of Gelre (1271-1326) also founded three new towns, Staverden, Hattem and Wijk, and Zutphen was expanded with the so-called Nieuwstad. Not much later the various local noblemen in the river area started building towns as centres of their domains. With the foundations of these towns the noblemen gave their domains urban centres, marking and, in particular, giving status to their sphere of power. The foundation of a new town, in town planning representing its function of power base, proved to be very attractive to many lords in the fourteenth century. Soon after Floris V and Reinoud I had given new impulses to the founding of bastion towns, this practice was taken up, at their own disadvantage, by local lords, by any one who had the means to do so, for instance, the bishops of Utrecht. Thus a pattern of towns was established, which had not grown naturally at favourably situated locations, but were deliberately founded and laid out by lords in accordance with preconceived plans.